‘A Difference in Typical Values’: Autistic Perspectives on Autistic Social Communication - Holly E. A. Sutherland; Sue Fletcher-Watson; Joseph Long; Catherine J. Crompton (Scandinavian Journal of Disability Research)
Autistic people socialise and communicate differently to non-autistic people. However, definitive accounts of what this social communicative style might look like, from an autistic perspective, have so far been limited. This qualitative research explored autistic people’s accounts of their own social communication behaviour and experiences of face-to-face interactions, to better understand the autistic social communicative style. Nine autistic adults (4 women, 1 nonbinary, 4 men; aged 23-70) took part in an online, forum-style focus group over the course of two weeks, participating in discussions about how they signalled (dis)interest and (un)enjoyment during conversations; what their natural social communication behaviours were; what talking to autistic people was like, compared to non-autistic people; and anything else they thought researchers should know. From this, five themes were developed: autistic experiences of self, attention, and environment; autistic expectations about how social interactions should work; conflicts between autistic and neurotypical-normative expectations; the constant effort of compensation and masking; and finding and creating shared understandings across neurotypes. Our findings highlight the complex interplay of autistic differences/difficulties with autistic people’s social environment, and emphasise the role that neurotypical-normative environments play in constructing autism as a social communication disability.